Exploring Attitudes and Perceptions: A Study of Green Banking and Sustainable Investment Among Undergraduate Students - Shrestha, Hira Lal; Chongbang, Numa; Shrestha, Sonika; Shrestha, Sushma; Neupane, Dasarath; Sejuwal, Narendra (International Journal of Atharva, 2025)
This study assesses undergraduate students’ perceptions of green banking and green investment in Kathmandu. Adopting quantitative methodology, the research employed a descriptive design and collected data via a structured Likert-scale questionnaire from 191 male and female students. The analysis revealed generally positive attitudes toward sustainable finance practices. Most respondents expressed concerns about green washing and emphasized the need for transparent reporting and adherence to international green investment standards. A strong interest in learning about green finance and support for integrating sustainability courses into university curricula was evident. Regarding green investment, awareness of sustainable options and institutional offerings was high, with media playing a key role in information dissemination. Ethical responsibility was prioritized over high returns by the majority, though willingness to invest in green projects and confidence in their profitability showed moderate levels. The findings highlight the students’ readiness to engage with green finance while underscoring the need for increased education, transparency, and institutional credibility to foster sustainable banking and investment practices in Nepal.